A Distributed Knowledge Approach to Managing Innovation - Kirkman, Dorothy Mary (Journal of Strategic Innovation and Sustainability, 2016)
The purpose of this paper is to discuss how organizations can manage innovation in a distributed environment where knowledge emerges from connections between actors and is never complete. Although this might may appear to be a daunting task, managing innovation in a distributed knowledge system is possible using the brain as a metaphor along with connectionist architecture. Integrating these two approaches improve innovation by enabling managers to model an organization's knowledge management strategies to contain brain-like connections that include redundancy and requisite variety, communications, and a decentralized control structure. These factors support knowledge transfer, trust, and heedful relationships among geographically and cognitively (functionally) distributed employees